Chapter Are Caulerpa species able to settle and develop on rhodolith beds? The case study of Marine Protected Area "Capo Carbonara" - Caronni, Sarah (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
The two green algae Caulerpa taxifolia (M.Vahl) C. Agardh and Caulerpa cylindracea Sonder, (Chlorophyta; Bryopsidales) are among the most invasive alien macroalgae in the Mediterranean Sea. The aim of this study was to investigate the presence and abundance of the three species on deep rhodolith bed of the Capo Carbonara Marine Protected Area MPA (Sardinia). The analysis of the collected data collected highlighted significant differences in the percent cover of the substratum among sampling sites and species with a significant presence of C. cylindracea at Santa Caterina slope